WBS-Based Method in Teaching Management Information Project - Yuling Su (Journal of Computer Networks and Communications)
In modern times, with the development of industrialized society and the invention of clocks and watches, people have become more and more concerned about institutionalization, and higher education time and space have also shown the characteristics of institutionalization. In modern times, educational informatization has brought challenges and opportunities for educational reform and development. The vigorous development of education informatization has also produced changes in higher education spatiotemporally. For example, the rise of catechism and online learning, the importance of fragmented time, the development of space toward virtualization, and the expansion of interactive space for interpersonal interactions. In addition, the enrichment and sharing of educational materials, the informatization, and big data of educational management also contribute to the improvement of time efficiency and optimization of time structure in higher education. With the background of education under the new normal, this paper briefly analyzes the current situation of education informatization construction in colleges and universities from the perspective of education managers, and addresses the current situation and problems of teaching management informatization construction, such as organizational structure dominated by pyramidal functional departments, inefficiency, inability to connect work, difficulty in work gap, difficulty in horizontal coordination, and closed information. A work breakdown structure (WBS) based project management theory and work structure decomposition method are proposed. This paper finds that the improved association rule mining algorithm can improve the efficiency of teaching management practice in colleges and universities by more than 14.58%, which is an important reference value for college management informatization.